2014
DOI: 10.1111/jbi.12354
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geological history on diversification in insular species: genetic and morphological patterns of Micromeria Benth. (Lamiaceae) in Tenerife (Canary archipelago)

Abstract: Aim Using phylogenetic and morphometric approaches, our study aims to understand the diversification process of the two groups of Micromeria species in Tenerife: the species restricted to the palaeoislands, and the species widely distributed in the younger part of the island. Location Tenerife, Canary Islands. Methods We calculated a calibrated phylogeny and a Neighbor‐Net network based on eight nuclear loci from 37 samples: 22 of the 8 species currently recognized in Tenerife, and 15 of their closest relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 33 publications
6
45
0
1
Order By: Relevance
“…The latter species, shown to be sister to Micromeria in the Canary Islands in previous phylogenetic analyses (Bräuchler et al, 2005(Bräuchler et al, , 2010Puppo et al, 2014), was used as outgroup. Only one sample from the taxon inhabiting Lanzarote and Fuerteventura (M. varia subsp.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter species, shown to be sister to Micromeria in the Canary Islands in previous phylogenetic analyses (Bräuchler et al, 2005(Bräuchler et al, , 2010Puppo et al, 2014), was used as outgroup. Only one sample from the taxon inhabiting Lanzarote and Fuerteventura (M. varia subsp.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Curto et al (2012) identified the loci by comparing EST sequences from several Lamiaceae species to the Arabidopsis thaliana genome and designing primers targeting potential intron regions. These markers were also used in Puppo et al (2014) and details concerning sequence structure can be found in Table 3. Amplification was performed using HotStarTaq Plus Master Mix Kit (QIAGEN, Valencia, California, USA) with a final volume of 10ul and containing 1 U Taq DNA polymerase, 75 nmol MgCl 2 , 1 nmol of each dNTP, 4 nmol of each primer, and ca.…”
Section: Amplification and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the data of Bräuchler et al (2010), section Pineolentia and section Micromeria have the same clade, and this shows that they have a common ancestor. The data of Puppo et al (2014Puppo et al ( , 2015 Bräuchler et al (2010). M. cymuligera (from section Cymularia) is closer to the Madagascarian group.…”
Section: Key To the Species Ofmentioning
confidence: 54%